2001
DOI: 10.1021/ie001002v
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability and Decomposition Products of Hexabromocyclododecane

Abstract: The thermal stability and decomposition products of hexabromocyclododecane (HBCD), a widely used aliphatic brominated flame retardant, were investigated. HBCD thermal degradation was carried out in nitrogen and in air at moderate heating rates (10 °C/min) using thermogravimetric analyzers and a laboratory-scale fixed-bed reactor. The identification of decomposition products was based mainly on FTIR and gas-chromatographic/mass-spectrometric techniques. Quantitative data on hydrogen bromide formation and on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(83 citation statements)
references
References 19 publications
1
81
0
1
Order By: Relevance
“…This indicates that stereoselective processes or isomer inter-conversion must occur at some point (Heeb et al, 2008b). As thermally labile compounds, HBCDs are subject to thermal rearrangement at temperatures above 160 C, resulting in the conversion of g-to a-HBCD, and thermal decomposition at temperatures above 240 C (Barontini et al, 2001). Inter-conversion was also proposed occurring at increased temperatures during the production or processing of HBCDcontaining materials (e.g., extruded polystyrene) (Heeb et al, 2008b;Köppen et al, 2008), which resulted in deviations from the relative abundance of HBCD diastereomers observed in the technical mixtures (e.g.…”
Section: Diastereomer Profiles Of Hbcdsmentioning
confidence: 99%
“…This indicates that stereoselective processes or isomer inter-conversion must occur at some point (Heeb et al, 2008b). As thermally labile compounds, HBCDs are subject to thermal rearrangement at temperatures above 160 C, resulting in the conversion of g-to a-HBCD, and thermal decomposition at temperatures above 240 C (Barontini et al, 2001). Inter-conversion was also proposed occurring at increased temperatures during the production or processing of HBCDcontaining materials (e.g., extruded polystyrene) (Heeb et al, 2008b;Köppen et al, 2008), which resulted in deviations from the relative abundance of HBCD diastereomers observed in the technical mixtures (e.g.…”
Section: Diastereomer Profiles Of Hbcdsmentioning
confidence: 99%
“…There are large differences in regards to the bioaccumulation potential among the individual diastereoisomers [2,10]. Previous studies found that ␥-HBCD can be transformed to ␣-HBCD at temperatures above 160 • C [11], and thus HBCD diastereoisomers cannot be separated by GC-MS and only total HBCD concentrations can be obtained by this method [12]. Liquid chromatography-mass spectrometry (LC/MS) and tandem mass spectrometry (LC/MS/MS) are found to easily separate HBCD diastereoisomers using reversed-phase columns [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…2(b)). Once the XPS board was heat-cut by a hot wire, HBCD diastereomers changed a little to 78%, 13%, and 9% for α-, β-, and γ-HBCD, respectively, which is close to thermal equilibrium (Peled et al, 1995;Barontini et al, 2001). Overall, compared to EPS, thermal cutting of XPS did not cause significant HBCD diastereoisomer conversion.…”
Section: Isomer Fractions Of Hbcdmentioning
confidence: 98%